ANALISIS PENGELOLAAN TANAH WAKAF PRODUKTIF DENGAN AKAD IJARAH UNTUK PERTANIAN BUAH NAGA (STUDI KASUS DI DESA SAMBIREJO KECAMATAN BANGOREJO) - M. Khanif Ardzani; M. Rifki Hidayat; Afria Rachmawati (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the management of productive waqf land in Sambirejo Village, Bangorejo District, with a focus on management through the ijarah contract as an economic innovation for the community, and its socio-economic impacts and challenges. The ijarah contract is implemented by leasing waqf land to farmers for dragon fruit cultivation, so that the assets can be utilized without changing ownership. The research method used is qualitative, with data collection through observation, interviews, and documentation with nazhir, farmers, and community leaders. The results show that waqf land management through the ijarah contract is effective as an innovation that turns passive assets into a source of income. This system creates economic independence for the community, increases farmer income, and expands social benefits through the distribution of waqf proceeds for religious activities. These findings are in line with the concepts of productive waqf and maqashid al-syariah in utilizing assets for the benefit of the community. However, challenges faced include limited managerial capacity, lack of institutional support, and low public literacy regarding productive waqf. Institutional strengthening and education strategies are needed for sustainable management.